MANAJEMEN LAYANAN PENDIDIKAN: ANALISIS PERAN KOMITE DAN FASILITAS SEKOLAH TERHADAP KEPUASAN SISWA - Aini, Nuril; Sutikno, Bambang; Wahyuni, Hari (Scimadly Publishing, 2025)
The quality of school management is largely determined by the contribution of various stakeholders, particularly the school committee and the effective utilization of facilities. However, many elementary schools still face challenges in facility management and limited committee participation in managerial functions. This study aims to analyze the influence of school committee involvement and school facilities on parent satisfaction at SDN Pekuncen, Pasuruan City. Using a quantitative approach, data were collected through questionnaires distributed to 88 parent respondents and analyzed using multiple linear regression. The findings reveal that both the school committee’s role and school facilities have a simultaneous and significant impact on parent satisfaction. Partially, each variable also demonstrates a positive and significant effect. These results suggest that strengthening the committee’s roles in advisory, support, liaison, and supervisory functions, alongside improving the quality and management of school facilities, can enhance parental satisfaction. The novelty of this study lies in its simultaneous examination of school committee involvement and facilities within the elementary education context, offering a new perspective on improving educational service quality in regional public schools.